Key Opinion Leader dalam Membangun Citra Jenama Almira Travel melalui Media Sosial - Nurafifah Lutfiah, Wanda; Haikal Wishnumurti, Rayhansyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The digital era has reshaped the marketing communication landscape, positioning Key Opinion Leaders (KOLs) as strategic actors in brand image development through social media. This research aims to explore how Almira Travel leverages KOLs as part of its digital communication strategy to build brand perception among audiences. Using a qualitative approach, data was collected through in-depth interviews with Almira Travel’s team and two collaborating KOLs Marissya Icha (@marissyaichareal) and Mimi Jamilah (@michan_91) and triangulated with other supporting sources. The findings indicate that emotional engagement, KOL credibility, and message-brand alignment significantly influence public perception of Almira Travel.